Canonical and Non-canonical Genomic Imprinting in Rodents - Kobayashi, Hisato (Frontiers in Cell and Developmental Biology, 2021)
Genomic imprinting is an epigenetic phenomenon that results in unequal expression of homologous maternal and paternal alleles. This process is initiated in the germline, and the parental epigenetic memories can be maintained following fertilization and induce further allele-specific transcription and chromatin modifications of single or multiple neighboring genes, known as imprinted genes. To date, more than 260 imprinted genes have been identified in the mouse genome, most of which are controlled by imprinted germline differentially methylated regions (gDMRs) that exhibit parent-of-origin specific DNA methylation, which is considered primary imprint. Recent studies provide evidence that a subset of gDMR-less, placenta-specific imprinted genes is controlled by maternal-derived histone modifications. To further understand DNA methylation-dependent (canonical) and -independent (non-canonical) imprints, this review summarizes the loci under the control of each type of imprinting in the mouse and compares them with the respective homologs in other rodents. Understanding epigenetic systems that differ among loci or species may provide new models for exploring genetic regulation and evolutionary divergence.